2010
DOI: 10.1111/j.1365-2427.2010.02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual effects of hypoxia on fish habitat quality in central Lake Erie

Abstract: SUMMARY1. Hypoxia occurs seasonally in many stratified coastal marine and freshwater ecosystems when bottom dissolved oxygen (DO) concentrations are depleted below 2-3 mg O 2 L )1 .2. We evaluated the effects of hypoxia on fish habitat quality in the central basin of Lake Erie from 1987 to 2005, using bioenergetic growth rate potential (GRP) as a proxy for habitat quality. We compared the effect of hypoxia on habitat quality of (i) rainbow smelt, Osmerus mordax mordax Mitchill (young-of-year, YOY, and adult), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 75 publications
(134 reference statements)
2
75
0
Order By: Relevance
“…The lake is home to a commercial coldwater fishery, with lake trout (Salvelinus namaycush) the most abundant fish species (Massol et al, 2007). The observed increase in water temperature and decrease in deep-water O 2 concentration combine to reduce the size and range of the coldwater fish habitat, a phenomenon referred to as the 'thermal-dissolved O 2 squeeze' (Coutant, 1985;Arend et al, 2010). Throughout Segments II and III in the Lake of Zurich, O 2 concentrations throughout the entire hypolimnion were below the hypoxic threshold for juvenile lake trout ([O 2 ] <7 mg l À1 ; Evans, 2007) at least once every year.…”
Section: Discussionmentioning
confidence: 99%
“…The lake is home to a commercial coldwater fishery, with lake trout (Salvelinus namaycush) the most abundant fish species (Massol et al, 2007). The observed increase in water temperature and decrease in deep-water O 2 concentration combine to reduce the size and range of the coldwater fish habitat, a phenomenon referred to as the 'thermal-dissolved O 2 squeeze' (Coutant, 1985;Arend et al, 2010). Throughout Segments II and III in the Lake of Zurich, O 2 concentrations throughout the entire hypolimnion were below the hypoxic threshold for juvenile lake trout ([O 2 ] <7 mg l À1 ; Evans, 2007) at least once every year.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of dissolved oxygen (DO) plays a vital role in biogeochemical cycling and the evolution of ecosystem structure and function and is also a sensitive indicator of physical and biogeochemical changes in aquatic ecosystems (Arend et al, 2011;Hupfer and Lewandowski, 2008;Jones et al, 2008;Vaquer-Sunyer and Duarte, 2008). For example, DO concentration controls phosphorus release from lake sediments (Hupfer and Lewandowski, 2008), oxycline depth (the greatest decrease in DO concentration at 1.0 m intervals) greatly influences hypolimnetic methylmercury (MeHg) concentrations (Perron et al, 2014), and hypoxia (DO concentration less than 6.5 mg/L) (Nü rnberg, 2004) in benthic water alters fish physiological processes, spatial distribution, and predatoreprey interactions (Pollock et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For this portion of the analysis, we used 3.0 mg·L −1 as the threshold for hypoxia. Although some studies have shown behavioral reactions at higher dissolved oxygen concentrations (Vaquer-Sunyer and Duarte 2008), this represented a median threshold for potentially unusable habitat for Lake Erie fishes based upon laboratory experiments on consumption (analyzed in Arend et al 2011). After visualizing the data and quantifying volumes, we determined that the hypoxic zones existed as a thin (ϳ2 m) layer contacting the bottom; therefore, we present only a two-dimensional view of bottom hypoxia herein (i.e., Fig.…”
Section: Determining Spatial and Temporal Variability Of Hypoxiamentioning
confidence: 99%
“…In contrast, the more pervasive effects appear to be indirect. Seasonal hypoxia leads to widespread reduction in habitat quality or loss of habitat as measured by reduced growth rate potential in bioenergetics models of temperature, oxygen, and forage density (Arend et al 2011;Brandt et al 2011). Loss of suitable habitat for positive growth is thought to be responsible for the observed declines in Lake Erie yellow perch (Perca flavescens) body condition following long durations of hypoxia (Scavia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation